Analysis of Community Knowledge, Attitudes, and Behaviors on Urban Heat Island Impacts in Rappocini District, Makassar City - Maru, Rosmini; Nasrul, Nasrul; Nur, Medar M; Musyawarah, Rahma; Amdah, Misdar; Sari, Nurmila (Universitas Negeri Gorontalo, 2026)
The phenomenon of Urban Heat Island (UHI) refers to the rise in temperature in urban areas compared to their surrounding rural regions, primarily due to land-use changes, reduced vegetation, and high-density infrastructure. This condition poses health and environmental risks and presents significant challenges for sustainable urban planning. This study aims to: (1) assess the community’s level of knowledge regarding climate change and the impacts of UHI; (2) analyze public attitudes and adaptive behaviors in responding to UHI; and (3) determine the influence of knowledge and attitudes on behavior related to mitigating UHI impacts. A quantitative approach was applied using a household survey and structured questionnaires. Data were analyzed using multiple linear regression, including t-tests, F-tests, and the coefficient of determination (R²), with the aid of SPSS software. The findings show that the community's knowledge and attitudes are generally categorized as good. The F-test yielded a significance value of 0.054, indicating that the model was nearly significant at the 0.05 level. Partially, attitudes had a significant influence on adaptive behavior (p = 0.030), whereas knowledge did not show a significant effect (p = 0.890). The coefficient of determination (R²) was 0.083, meaning that knowledge and attitudes collectively explain 8.3% of the variation in community behavior toward UHI mitigation. These findings highlight the need to strengthen public education and promote behavioral adaptation strategies to reduce the environmental impact of urban heat.